Digging into the Pocketbook: Evidence on Economic Voting from Income Registry Data Matched to a Voter Survey - Andrew J. Healy; Mikael Persson; Erik Snowberg (Center for Economic Studies and ifo Institute (CESifo), 2016)
We combine fine-grained data on voters' personal financial records with a representative election survey to examine three central topics in the economic voting literature: pocketbook versus sociotropic voting, the effects of partisanship on economic views, and voter myopia. First, these data show that voters who appear in survey data to be voting based on the national economy are, in fact, voting equally on the basis of their personal financial conditions. Second, there is strong evidence of both partisan bias and economic information in economic evaluations, but fine-grained financial data is required to separate the two. Third, although in experiments, and aggregate historical data, voters appear focused on recent economic conditions when choosing how to vote, we find no evidence of myopia when examining actual personal economic data. Collectively, the results show our understanding of economic voting depends crucially on the quality of available data.
Keywords: 330